A general strategy based on the self-evolution of building blocks for the construction of one-dimensional hierarchically super-structured TiO2 fibres. Issue 26 (19th June 2020) - Wang, Yun; Huang, Haibo; Du, Daoguang; Dong, Yanfeng; Feng, Zhongmin; Wang, Yuanpeng; Sun, Ting; Xu, Yan
Abstract : We provide a general strategy based on the self-evolution of building blocks to fabricate one-dimensional hierarchically superstructured metal-doped titanate and TiO2 materials with coated-nanosheet and interconnected meso-/macropores. Abstract : One-dimensional hierarchically superstructured metal-doped titanate and TiO2 materials with coated-nanosheet and interconnected meso-/macropores have been successfully constructed via a general strategy based on the self-evolution of building blocks. The as-fabricated superstructured TiO2 -based fibers exhibited remarkable stable cycling performance at a high current rate (5C) in lithium–sulfur (Li–S) batteries.